The Influence Of Facilities and Location On Customer Satisfaction at Han’s Cafe Lahat - Gita Suci; Heri Fitriadi; Delvina Yulanda (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of facilities and location on customer satisfaction at Han's Cafe Lahat. The type of research used is associative with a quantitative approach. The research variables consist of: facilities (X1) and location (X2) as independent variables, and customer satisfaction (Y) as the dependent variable. All variables are measured using a Likert scale. The number of samples studied was 97 respondents. Instrument testing using validity and reliability tests. The data analysis tool used is multiple linear regression with the help of the SPSS Version 25 application program. The results of this study show the following regression line: Y = 0.083 + 0.363 + 0.629. The R square value (determination coefficient) is 0.896 or 89.6%. The results in this study indicate that partially facilities affect customer satisfaction and location also affects customer satisfaction. Simultaneously, it is proven that facilities and location affect customer satisfaction. Therefore, we recommend that the owner of Han's Cafe Lahat make improvements to its facilities and location.